“Lezibian/mulezi”: Adoption of “globalized” lesbian identity and secondary self-labels among same-sex attracted women in Harare - Muparamoto, Nelson (Journal of Lesbian Studies, 2022)
Drawing from ethnographic research, incorporating informal conversations, semi-structured interviews and a focus group discussion, the paper explores the subjective meanings and construction of the “lesbian” identity in a “hostile” environment among selected same-sex attracted women in Harare. While the globally circulating identity labels are loaded with historical baggage which can be limiting or confusing in non-western contexts, most of the study participants related to some of the labels that are prominent in the present-day, western-inspired global discourse on same-sex relations. Self-styling and the quest to exhibit masculine decorum was a central aspect in the narratives of most “butch” identifying women. For most butch identifying women being lesbian was closely interwoven with considerations about one’s gendered self. However not all participants were comfortable with the circulating identity labels as they found them restrictive and loaded. While subjective preferences of the participants demonstrate complexity in how “lesbianism” is locally constructed and experienced, the lesbian identity is certainly not obsolete in Harare among same-sex attracted women.
Keywords: afrique; butch; corps; personnes lesbiennes; ressource en ligne; régions géographiques; sexualité; thématiques; zimbabwe

La Philistine - Leila Marshy (Linda Leith, 2021)
Lorsque Nadia Eid quitte Montréal, laissant derrière elle son amoureux, pour aller à la recherche de son père palestinien ayant disparu au Caire depuis des années, elle est loin de s’imaginer qu’elle y trouvera aussi une relation torride et complexe avec une jeune artiste égyptienne. Mais que faire quand nationalité et relations personnelles refusent de coexister? Pendant que l’intifada fait rage de l’autre côté de la frontière, Nadia devra choisir entre famille et destinée.
Keywords: afrique; amériques; asie; corps; egypte; palestine; personnes lesbiennes; québec; roman; régions géographiques; sexualité; thématiques; violences

Empowerment as a disabled, black woman - Oliver, Kym; Abdullahi, Jumoke (2020)
The dynamic duo of Jumoke and Kym tackle the topic of empowerment and what that means for disabled, Black women. This was filmed as part of a TEDx talk at the University of Sussex in England. _______________________________________________________________________________________________ TRIPLE CRIPPLES was created by @TheKymOliver & @JayOnLife to provide a platform for & highlight the narratives of Black & non-Black Women, Femmes & Non-Binary people of colour, living with disabilities. We are here. We exist! We know the media and mainstream disability conversations would have you believe otherwise mega eye roll*... But guess what? WE GOTS THA INTERNETS, BITCHEZZZZ!!! Eat it. *put on shades and look cool at night ———————————————————————————————- JOIN US ON OUR JOURNEY! Hit the comments box! And if you or any women/femmes/non-binary people you know, would like to be a guest... Hit the DM’s! 🖤 Website: https://thetriplecripples.uk/ Twitter/Instagram: @TripleCripples Follow Jumoke: @JayOnLife Follow Kym: @TheKymOliver ———————————————————————————————- Track: “runaway” ~ K15 feat. AMA LIVE! Big Love to K15 for kindly letting us use his amazing music as our bedding track!!! Check out @k15music, support his sound, buy some vinyls and follow him on all platforms: Twitter: @K15music Facebook: @K15music Soundcloud: @K15 Bandcamp: @K15music
Keywords: 2000-2029; afrique; amériques; approches et analyses; capacitisme; caraïbes; corps; discours dominant; empowerment; europe; fem3300; femmes* noires; invisibilité; militance; premier cycle; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; systèmes d'oppression; thématiques

Living a feminist life - Ahmed, Sara (Duke University Press, 2017)
In Living a Feminist Life Sara Ahmed shows how feminist theory is generated from everyday life and the ordinary experiences of being a feminist at home and at work. Building on legacies of feminist of color scholarship in particular, Ahmed offers a poetic and personal meditation on how feminists become estranged from worlds they critique-often by naming and calling attention to problems-and how feminists learn about worlds from their efforts to transform them. Ahmed also provides her most sustained commentary on the figure of the feminist killjoy introduced in her earlier work while showing how feminists create inventive solutions-such as forming support systems-to survive the shattering experiences of facing the walls of racism and sexism. The killjoy survival kit and killjoy manifesto, with which the book concludes, supply practical tools for how to live a feminist life, thereby strengthening the ties between the inventive creation of feminist theory and living a life that sustains it. https://www.saranahmed.com/
Keywords: 2000-2029; 2010-2019; afrique; approches et analyses; care; corps; discipline; fem1000; feminisme noir; incontournable; intersectionnalité; manifeste; militance; occident; orient; philosophie; premier cycle; périodes historiques; racisme; ressource en ligne; régions géographiques; sciences humaines; sexisme; systèmes d'oppression; thématiques; violences; émotions; études culturelles

« Combien de temps pour devenir une femme ? » Sujétion et transgression chez Nina Bouraoui - Husung, Kirsten (Expressions maghrébines, 2017)
Cet article montre dans quelques œuvres d'inspiration autobiographique de Nina Bouraoui comment la subjectivité de la protagoniste est construite par différents discours identitaires dans le cadre franco-algérien et comment elle est déconstruite ou reconstruite par l'écriture. L'expérience corporelle de la protagoniste porte l'empreinte de l'héritage familial qui est le microcosme de l'héritage culturel marqué par la violence de l'Histoire franco-algérienne. En outre, l'emprise de la normalisation des genres pèse lourd sur la subjectivité de la protagoniste, ce qui résulte dans des sentiments d'auto-culpabilisation. L'entre-deux, c'est-à-dire entre deux pays et deux genres, est pourtant l'espace à la fois douloureux et créatif qui donne la force d'écrire et de s'écrire, et de venir à bout du sentiment de culpabilité, ce qui est analysé à l'aide de la lecture par Judith Butler du mythe d'Antigone et de la performativité de la confession.
Keywords: afrique; algérie; corps; europe; france; genre; histoire et politique; identités LGBTQIA2+; personnes lesbiennes; ressource en ligne; régions géographiques; sexualité; thématiques; violences

Le ventre des femmes : capitalisme, racialisation, féminisme - Vergès, Françoise (Albin Michel, 2017)
Dans les années 1960-1970, l'État français encourage l'avortement et la contraception dans les départements d'outre-mer alors même qu'il les interdit et les criminalise en France métropolitaine. Comment expliquer de telles disparités? Partant du cas emblématique de La Réunion où, en juin 1970, des milliers d'avortements et de stérilisations sans consentement pratiqués par des médecins blancs sont rendus publics, Françoise Vergés retrace la politique de gestion du ventre des femmes, stigmatisées en raison de la couleur de leur peau. Dès 1945, invoquant la «surpopulation» de ses anciennes colonies, l'État français prône la régulation des naissances et l'organisation de l'émigration; une politique qui le conduit à reconfigurer à plusieurs reprises l'espace de la République, provoquant un repli progressif sur l'Hexagone au détriment des outre-mer, où les abus se multiplient. Françoise Vergés s'interroge sur les causes et les conséquences de ces reconfigurations et sur la marginalisation de la question raciale et coloniale par les mouvements féministes actifs en métropole, en particulier le MLF. En s'appuyant sur les notions de genre, de race, de classe dans une ère postcoloniale, l'autrice entend faire la lumière sur l'histoire mutilée de ces femmes, héritée d'un système esclavagiste, colonialiste et capitaliste encore largement ignoré aujourd'hui.
Keywords: 1900-1999; 1960-1969; 1970-1979; afrique; approches et analyses; corps; discours dominant; europe; fem3100; feminisme décolonial; france; maternité; premier cycle; périodes historiques; racisme; régions géographiques; sexisme; système colonial; systèmes d'oppression; thématiques; violences; île de la réunion

Révéler l'étoffe : Alger - Oran - Constantine - Tizi Ouzou - Tamanrasset - Paris - Maya-Ines Touam - Touam, Maya-Ines (2014)
Révéler l’étoffe est un travail né en réaction à la photographie orientaliste du xixe siècle. Les cartes postales des femmes des régions du MOAN notamment les réduisaient à un simple objet de curiosité. Réalisée à Alger, à Oran, à Constantine, ...
Keywords: afrique; algérie; arts; corps; discipline; fem3100; femmes algériennes; histoire; photographie; premier cycle; ressource en ligne; régions géographiques; textiles; thématiques

Chuchote pas trop - Ekotto, Frieda (L'Harmattan, 2005)
"Les jeunes filles de Fulani sont enfermées ainsi, parfois pendant des années, dans l'obscurité, jusqu'à leur mariage imposé." A travers des portraits de femmes aux destins rebelles, de conflits de cultures, Frieda Ekotto bouscule les préjugés pour nous proposer une autre vision des rapports humains. Riche de son écriture composite, éclaté, ce récit échappe ainsi aux formes traditionnelles de la narration.
Keywords: afrique; cameroun; corps; littérature; ressource en ligne; roman; régions géographiques; sexualité; thématiques; violences